Hubungan Faktor Ergonomi dengan Keluhan Musculuskeletal Disorders (MsDs) pada Pekerja Pembuatan Ulos - Ros Perdawina Simorangkir; Santy Deasy Siregar; Eva Ellya Sibagariang (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
Musculoskeletal disorders (MSDs) are complaints that occur in parts of the muscleskeletal felt by someone ranging from a very mild complaint to very heavy complaints. One factory that has a risk of causing MSDs is Ulos factory. From the results of initial survey observations on 26 and 27 August 2019 at Siatas Barita Subdistrict, North Tapanuli Regency there were 75 workers, which at the time In the initial survey I interviewed 25 workers using a questionnaire and observations and results that can be obtained there are 20 workers experiencing complaints MSDs, especially in the neck, waist, buttocks, and calves. The purpose of this study is to find out Relationship of Ergonomic Factors with Musculoskeletal Disorder (MSDS) Complaints in Workers Making Ulos in Siatas Barita Subdistrict, North Tapanuli Regency in 2019. Type This research is an analytic survey with cross sectional design. Research population is a number of weaving workers in Siatas Barita District, North Tapanuli Regency 75 people. The research sample is workers in Enda Portibi Village, Siatas Barita District North Tapanuli Regency numbered 75 people, obtained using total sampling. The results of this study were analyzed using the chi square test with significance 95% (0.05). The results showed that there was a relationship between work duration, work period, work posture, with complaints of Musculoskeletal Disorders in workers making ulos with each chi-square test results obtained p value 0.029, 0.005, 0.004, The conclusion of this research is that there is a relationship between the length of work, length of service, posture Working with complaints of Musculoskeletal Disorders of weaving workers in the District of Siatas Barita North Tapanuli Regency in 2020.